Mentha rotundifolia (L.) Huds. and Salvia officinalis L. hydrosols mitigate aging related comorbidities in rats - Boualam, Khadija; Ibork, Hind; Lahboub, Zakaria; Sobeh, Mansour; Taghzouti, Khalid (Frontiers in Aging Neuroscience, 2024)
Aging is often linked to oxidative stress, where the body experiences increased damage from free radicals. Plants are rich sources of antioxidants, playing a role in slowing down aging and supporting the proper functioning and longevity of cells. Our study focuses on exploring the impact of Mentha rotundifolia (MR) and Salvia officinalis (SO) hydrosols on aging-related comorbidities. The chemical composition of MR and SO hydrosols was analyzed by gas chromatography coupled to mass spectrometry. 2,2-Diphenyl 1-picrylhydrazyl and 2,20-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid radicals scavenging assays were used to assess their in vitro antioxidant activity, and heat induced albumin denaturation test was used to evaluate their anti-inflammatory activity. Subsequently, we administered 5% of each plant hydrosol in the drinking water of 18-month-old rats for six months. We then conducted behavioral tests, including open field, dark/light box, rotarod, and Y-maze assessments, and measured biochemical parameters in plasma, liver and brain tissues. At two years old, animals treated with MR and SO hydrosols displayed fewer physical and behavioral impairments, along with well-preserved redox homeostasis in comparison with animals in the control group. These results highlighted the significance of MR and SO hydrosols in addressing various aspects of age-related comorbidities. The study suggests that these plant-derived hydrosols may have potential applications in promoting healthy aging and mitigating associated health challenges.